An Uncrossable Rubicon: Liszt's Sardanapalo Revisited. Issue 2 (3rd July 2018) - Trippett, David
Abstract: In 1850, after five years of planning, Liszt began composing music for his Italian opera, Sardanapalo, after Byron. It was central to his ambition to attain status as a European composer, but he abandoned the project halfway through. La Mara (1911), Humphrey Searle (1954) and others declared the manuscript fragmentary and partially illegible, but in 2016 this verdict was categorically overturned when work began on an edition of what Liszt notated: almost the entirety of Act 1. This article draws on an array of sources – published and unpublished – significantly to update our knowledge of the circumstances surrounding Liszt's composition and abandonment of Sardanapalo . In light of his inconsistently Italianate music and idiosyncratic treatment of the libretto, it also reinterprets Liszt's mid-century aesthetic orientation, as a confidant of Wagner and would-be pillar of Franz Brendel's future neudeutsche Schule . By contextualizing key aspects of the uncovered musical score and libretto within Liszt's mid-century writings on aesthetics, it posits character, declamatory melody and the visuality of the stage as (initially) critical criteria in the communication of a literary narrative, and suggests that Liszt's impulse towards symphonic poetry may first have been kindled within the aesthetic potential of opera.